Agonal Thrombi at Autopsy. (September 2015) - Hansma, Patrick; Powers, Stephanie; Diaz, Francisco; Li, Wei
<x xml:space="preserve">Abstract</x> Abstract Clots and thrombi identified at autopsy are generally classified dichotomously as antemortem or postmortem. Current articles and textbooks support this approach. Earlier literature often contained descriptions of a third category, the agonal thrombus that forms while the patient is dying. We collected 238 autopsy cases including 80 rapid/sudden deaths by violence and 21 (including 1 pediatric) deaths from acute pulmonary emboli. We analyzed the gross and microscopic features of clots and thrombi. Agonal thrombi were identified in 122 cases (89% of cases of "slow" death). Agonal thrombi were not identified in cases of sudden death. We found that a comprehensive description of the macroscopic features was a key to interpretation. The gross and microscopic features of agonal thrombi "chicken fat" support their hybrid nature. The dichotomous classification of clots and thrombi seems to be founded on assumptions of clinical significance but is perhaps oversimplified. Agonal thrombi area distinct class of thrombus that, although not clinically significant as an immediate cause of death, arises by its own mechanisms and has its own morphology. It is advisable to avoid classifying agonal thrombi as mere postmortem clots because in forensic cases, they may help support an argument against sudden death.